Skutterudites as thermoelectric materials: revisited. Issue 52 (10th June 2015) - Rull-Bravo, M.; Moure, A.; Fernández, J. F.; Martín-González, M.
<x xml:space="preserve">Abstract</x> A review of the progress on skutterudites over the last years and future prospects.